An Examination of Teacher's Pedagogical Philosophical Beliefs of Secondary Science Teachers in Sofia Public Schools, Sofia, Bulgaria - E. Boiadjieva; A. Tafrova-Grigorova; J.E. Hollenbeck; M. Kirova (University of Sofia, 2009)
This investigation sought understand of the pedagogical philosophies of Bulgarian secondary science teachers in public schools in Sofia, Bulgaria, using the instrument that derived information for this study was an interview protocol consisting of six open-ended questions, with a numerical scoring analysis: the Teachers Pedagogical Philosophy Interview (TPPI). A review of literature shows there is no research on the pedagogical philosophical basis of teacher's beliefs on teaching or on the effect of integrating constructivist teaching methodology in Bulgarian secondary science classrooms.